Assessment of Social-Emotional Competencies in Primary and Secondary School Students: Theoretical Models, Assessment Methods, and Evaluation Tools - Hou Yongmei (Language, Literature and Education: Research Updates Vol. 1, 2025)
Background: The cultivation of social-emotional competencies is not only a necessary condition for academic development and mental health construction among primary and secondary school students but also an important way to enhance their subjective well-being. Objective: To understand the theoretical model and main assessment methods of social-emotional competence among primary and secondary school students, and analyze future research directions. Methods: Using the keywords "primary school students" or "middle school students" and "social and emotional competence", a literature search was conducted in Pubmed, Web of Science, CINAHL Plus, Scopus, Embase, PsycINFO, and CNKI for empirical papers published in English or Chinese in the past 10 years. Results: A total of 39 papers were included. Previous literature indicates that the social-emotional competence of primary and secondary school students worldwide tends to decrease, and students from low socioeconomic backgrounds experience a faster decline in social-emotional competence. The connotation of social-emotional competence is complex and multidimensional, with strong cultural dependence, and there is no unified conceptual definition to date. Various assessment methods have their advantages and limitations. Although assessment tools have been widely developed and have yielded many achievements, there are significant differences in the number and connotation of measurement dimensions, as well as the psychometric performance of the tools, which affect the comparability and generalizability of assessment results. Conclusion: Standardized assessment is a key link in the research and cultivation of social-emotional competence. However, issues such as the definition of the concept of social-emotional competence and the optimization of assessment methods, as well as the scientific development and rational selection of assessment tools, still need further exploration.